JON FOSSE'S WRITINGS READ THROUGH NORWEGIAN AND ROMANIAN LENSES. A SURVEY - TOMESCU BACIU, Sanda; DREVE, Roxana-Ema (Studia Universitatis Babeș-Bolyai Philologia, 2023)
On the occasion of the recent Nobel Prize for Literature 2023, awarded to the Norwegian playwriter, novelist, essay writer and poet Jon Fosse, we invited scholars and translators from Norway and Romania to answer a series of questions related to Jons Fosse’s outstanding contribution to world literature. Many of the translators are at the same time active at academic level. The researchers and the translators were asked to address at least three of several questions. We invited the following contributors to participate in the survey: Professor Heming H. Gujord (Bergen University), Professor Unni Langås (Agder University), Professor Lisbeth P. Wærp and Professor Henning H. Wærp (The Artic University of Norway), Associate Professor and translator Zsofia Domsa (Norwegian University of Science and Technology, NTNU, Trondheim), Associate Professor and translator Carmen Vioreanu (Bucharest University), Senior Lecturer and translator Daria Ioan (Babeș-Bolyai University, Cluj), Assistant Professor and translator Ovio Olaru (Lucian Blaga University, Sibiu) and Dr. Anamaria Babiaș-Ciobanu, translator. We are thankful to the respondents for participating in the survey.